How Polycentric is a Monocentric City? The Role of Agglomeration Economies - Gabriel M. Ahlfeldt; Nicolai Wendland (Economics and Econometrics Research Institute (EERI), 2010)
Can the demise of the monocentric economy across cities during the 20th century be explained by decreasing transport costs to the city center or are other fundamental forces at work? Taking a hybrid perspec¬tive of classical bid-rent theory and a world where clustering of economic activity is driven by (knowledge) spillovers, Berlin, Germany, from 1890 to 1936 serves as a case in point. We assess the extent to which firms in an environment of decreasing transport costs and industrial transformation face a trade-off between distance to the CBD and land rents and how agglomeration economies come into play in shaping their location deci¬sions. Our results suggest that an observable flattening of the traditional distance to the CBD gradient may mask the emergence of significant agglomeration economies, especially within predominantly service-based inner city districts.
Keywords: N7; N9; R33; O12; 330; Transport Innovations; Land Values; Location Productivity; Agglomeration Economies; Economic History; Berlin